Breastfeeding in Mothers with Multiple Sclerosis: The German Experience - Aigner, Stefanie; Huhn, Konstantin; Cepek, Lukas; Hellwig, Kerstin; Nickel, Florian; Bayas, Antonios (Breastfeeding Medicine, 2023)
Background: Many female people with multiple sclerosis (pwMS) are in childbearing age; however, only few data exist about the situation of breastfeeding in pwMS.Objective: Our study analyzed breastfeeding rate and duration, reasons for weaning, and the impact of disease severity on successful breastfeeding in pwMS.Methods: The study included pwMS giving birth within 3 years before study participation. Data were collected by structured questionnaire.Results: Compared to published data, we found a significant difference (p = 0.0007) between the nursing rate in the general population (96.6%) and females with MS (85.9%). However, a higher rate of exclusive breastfeeding could be observed in our study population for 5-6 months in 40.6% of pwMS versus 9% for 6 months in the general population. In contrast, total breastfeeding duration in our study population was shorter (18.8% for 11-12 months) than in the general population (41.1% for 12 months). Reasons for weaning were predominantly (68.7%) related to breastfeeding barriers based on MS. No significant impact of prepartum or postpartum education on the breastfeeding rate could be observed. Prepartum relapse rate and prepartum disease-modifying drugs had no effect on breastfeeding success.Conclusion: Our survey provides an insight into the situation of breastfeeding in pwMS in Germany.
CRIS-Team WoS Importer:2023-03-17